Variability, correlation and path coefficient analysis in fenugreek (Trigonella foenum- graecum L.) under water limited conditions - L K Dashora, Abhay Dashora, S R Maloo (Journal of Spices and Aromatic Crops, 2011)
Genetic variability, character association and path analysis between yield and its component traits were carried out in 48 genotypes of fenugreek (Trigonella foenum graecum) at Udaipur (Rajasthan). Highly significant differences between genotypes were recorded for all the characters studied. High phenotypic and genotypic coefficient of variation coupled with high heritability and high genetic advance was observed for seed yield plot-1, biological yield plot-1, harvest index and pods plant-1 indicating the importance of additive gene effects for these traits. Biological yield plot-1 and harvest index exhibited positive and significant correlation with seed yield while days to 50% flowering exhibited negative and significant association with seed yield. Path coefficient analysis revealed that biological yield plot-1 had highest positive direct effect on seed yield followed by branches plant-1, pod length and test weight. It was concluded that improvement in the seed yield of fenugreek is possible through selection for biological yield plot-1, harvest index, branches plant-1, pod length and test weight.